2017
DOI: 10.1556/1326.2017.29.3.07
|View full text |Cite
|
Sign up to set email alerts
|

HPLC analysis and blood-brain penetration of 20-hydroxyecdysone diacetonide

Abstract: Summary. Blood-brain penetration of 20-hydroxyecdysone 2,3;20,22-diacetonide (20DA) has been scouted using chromatographic methods. In vivo experiments were performed by treating male Wistar rats intraperitoneally (i.p.) with a dose of 50 mg kg −1 20DA. Control experiment was done by using 20-hydroxyecdysone (20E). Definite brain penetration of 20DA was found by using high-performance liquid chromatography (HPLC), while 20E does not show this type of distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Moreover, in a most recent study from our group, 20 was found to have significantly prolonged pharmacokinetics in rats as compared to that of the rapidly eliminating 20E, which suggests an increased metabolic stability [69]. These findings provide further support to the presumption that ecdysteroid dioxolanes should be stable enough to retain their biological activity throughout the metabolic process, and therefore the preparation of novel ecdysteroid dioxolanes deserves further attention.…”
Section: Previous Studies Of Our Group Substantiating the Present Worksupporting
confidence: 56%
“…Moreover, in a most recent study from our group, 20 was found to have significantly prolonged pharmacokinetics in rats as compared to that of the rapidly eliminating 20E, which suggests an increased metabolic stability [69]. These findings provide further support to the presumption that ecdysteroid dioxolanes should be stable enough to retain their biological activity throughout the metabolic process, and therefore the preparation of novel ecdysteroid dioxolanes deserves further attention.…”
Section: Previous Studies Of Our Group Substantiating the Present Worksupporting
confidence: 56%
“…However, studies on rats after i.p. injections of ecdysteroids show that although 20E diacetonide will cross the blood-brain barrier, 20E itself does not (Kalász et al 2017).…”
Section: Anti-stressmentioning
confidence: 99%